Convergent epicardial‐endocardial ablation for treatment of long‐standing persistent atrial fibrillation: A review of literature. Issue 6 (25th April 2020) - Khan, Zoheb; Hamandi, Mohanad; Khan, Hafiza; DiMaio, John Michael; Evans, Matthew
Abstract: Background and Aim of study: The convergent procedure (CVP) is a hybrid ablation technique via a subxiphoid incision that has recently emerged as a treatment option for non‐paroxysmal atrial fibrillation (npAF). By combining endocardial and epicardial ablation into a simultaneous or staged procedure, the pulmonary vein and posterior left atrium can be isolated with transmural lesion sets while minimizing the risk of proarrhythmic gaps that are a known limitation with endocardial linear lesion sets. We reviewed the 12‐month outcomes in patients who underwent CVP compared to those who underwent endocardial catheter ablation (CA) and surgical ablation (SA). Methods: A literature search was conducted using the PubMed database for publications related to CVP. Selected studies included detailed 12‐month follow‐up of patients, patient characteristics, periprocedural complications, use of antiarrhythmic drugs (AADs), and monitoring method. Results: Five studies with 340 patients who underwent CVP between January 2009 and March 2017 were selected for this review. A total of 8.5% of patients had paroxysmal AF (pAF), 42.2% had persistent AF (peAF), and 49.1% had long‐standing persistent AF (lspAF). At 12 months, 81.9% of patients were in sinus rhythm, while 54.1% of patients were in sinus rhythm while not taking AADs. The overall complication rate was 10%. Conclusion: CVP had better 1‐year efficacy in eliminating AF when compared to CA. However, SA, specifically the Cox Maze IV, had lower rates of AF recurrence in the npAF patient population. Despite its promising 1‐year efficacy rates, the periprocedural complication rate for CVP was significantly higher than both CA and SA.